2019
DOI: 10.1002/aoc.5281
|View full text |Cite
|
Sign up to set email alerts
|

Aminated metal‐organic framework (NH2‐MIL‐101(Cr)) incorporated polyvinylidene (PVDF) hybrid membranes: Synthesis and application in efficient removal of Congo red from aqueous solution

Abstract: The efficient treatment of wastewater containing organic dyes generated in diverse industrial processes has become more crucial owing to increasing environmental concerns. In this paper, we incorporated the aminated functional NH2‐MIL‐101(Cr) into the porous polyvinylidene fluoride (PVDF) to fabricate the MOFs/polymer hybrid membranes, which combined the surface activity of MOFs and the membrane's filtration plus the adsorption process, and can be used in the high‐efficient removal of congo red (CR) from aqueo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…158 For instance, Tan et al prepared MOF–polymer hybrid membranes by incorporating functionalized NH 2 -MIL-101 (Cr) into porous PVDF using a co-blending method. 159 The –NH 2 groups in the CR dye and NH 2 -MIL-101 (Cr) undergo chemisorption through hydrogen bonding. Incorporating the MOF particles improves the membrane's hydrophilicity and porosity, achieving good adsorption separation of dye wastewater.…”
Section: Types Of Mof Hybrid Membranementioning
confidence: 99%
“…158 For instance, Tan et al prepared MOF–polymer hybrid membranes by incorporating functionalized NH 2 -MIL-101 (Cr) into porous PVDF using a co-blending method. 159 The –NH 2 groups in the CR dye and NH 2 -MIL-101 (Cr) undergo chemisorption through hydrogen bonding. Incorporating the MOF particles improves the membrane's hydrophilicity and porosity, achieving good adsorption separation of dye wastewater.…”
Section: Types Of Mof Hybrid Membranementioning
confidence: 99%
“…The formation of the protective hydration layer due to the h-BN and TiO 2 functionalized chromium-benzenedicarboxylate metalorganic framework MIL-101(Cr) based photocatalyst on the Environmental Science: Water Research & Technology Paper membrane surface enhanced the water contact angle, which simultaneously favors the high flux and improves the antifouling characteristics of the membranes. 29,30 In addition, the hydrophilicity of resultant membranes is enhanced by the surface modification with h-BN and TiO 2 functionalized MIL-101(Cr) and the presence of oxygen containing groups in nanoparticles. It is observed that the surface hydrophilicity of the photocatalytic h-BN functionalized MIL-101(Cr) PVDF is very high compared to the other photocatalytic PVDF MMMs.…”
Section: Hydrophilicity Of the Pvdf Mmmsmentioning
confidence: 99%
“…So far, a large number of chemical, physical, and biological methods have been used to remove dyes from wastewater, such as ion exchange, chemical oxidation, flocculation, chemical coagulation, curing, photocatalytic degradation, biodegradation, advanced oxidation, membrane separation, and adsorption . Among them, the adsorption method has the advantages of low cost, safety, simplicity, and easy recovery.…”
Section: Introductionmentioning
confidence: 99%
“…6 Therefore, to reduce the harm to the ecological environment and human health, it is very important to find a practical, convenient, and rapid wastewater treatment method. So far, a large number of chemical, physical, and biological methods have been used to remove dyes from wastewater, 7−9 such as ion exchange, 10 chemical oxidation, 11 flocculation, 12 chemical coagulation, 13 curing, 14 photocatalytic degradation, 15 biodegradation, 16 advanced oxidation, 17 membrane separation, 18 and adsorption. 19 Among them, the adsorption method has the advantages of low cost, safety, simplicity, and easy recovery.…”
Section: ■ Introductionmentioning
confidence: 99%